479 Safety and effectiveness of left atrial appendage occlusion in patients with chronic kidney disease. (8th December 2021) - Magnocavallo, Michele; Rocca, Domenico Giovanni Della; Lavalle, Carlo; Chimenti, Cristina; Carola, Gianni; Mohanty, Sanghamitra; Trivedi, Chintan; Bassiouny, Mohamed; Al-Ahmad, Amin; Burkhardt, David J; Gallinghouse, Joseph G; Sanchez, Javier E; et al.
Abstract: Aims: Left atrial appendage occlusion (LAAO) might be particularly attractive in chronic kidney disease (CKD) patients, owing to a high thromboembolic risk and an even higher risk of bleeding. We sought to evaluate the safety and effectiveness of LAAO in CKD patients. Methods and results: A total of 1238 patients undergoing LAAO at six centres were enrolled. On the basis of kidney function, as assessed via the CKD-EPI formula, patients were classified in two groups. Group1 had a GFR value ≤60 ml/min/1.73 m 2 (CKD stages 3a-b, 4, and 5), whereas Group2 had a function >60 ml/min/1.73 m 2 (CKD stages 1 and 2). Predicted annual rates of TE or major bleeding events were compared to the annualized observed risk of the two populations. Compared to Group 2 ( n = 720, 47.5% males), patients in Group 1 ( n = 518, 86.5% males) were older (mean age: 78 ± 8 vs. 75 ± 8, P < 0.001), and were at higher risk (CHA2DS2-VASc: 4.7 ± 1.4 vs. 4.4 ± 1.4; HAS-BLED: 3.8 ± 1.1 vs. 3.2 ± 1.0; P < 0.001 for both). Procedural complications (within 7 days) were observed in 3.1% of patients in Group1 and 4.6% of those in Group2 ( P = 0.18); of them, major procedural adverse events occurred in 10 patients of Group1 [1.9%; four gastrointestinal (GI) bleedings, four tamponades, one myocardial infarction, one retroperitoneal hematoma] and in 15 (2.1%; seven pericardial tamponades, five retroperitoneal hematomas, two strokes, and one GI bleeding) of Group2 ( P = 0.84). During a mean follow-up of 11.5 ± 7 months (1183 pt/years), 10 stroke/TIA (1.9%) and 25 major bleeding events (4.8%; 18 GI and 7 intracranial) were observed in Group1. Rate of TE events was not statistically different between groups (1.9% vs. 2.6%; P = 0.41); major bleedings had a significantly higher incidence in Group 1 (4.8% vs. 2.4%, P = 0.02). Based on the estimated annual TE risk according to the CHA2DS2-VASc score (4.76% in Group1 and 4.51% in Group 2), the % risk reduction after LAAO was 57.5% and 38.8%, respectively. Based on the estimated annual major bleeding risk based on the HAS-BLED score (7.31% in Group1 and 5.39% in Group2), the % bleeding risk reduction was 30.9% and 54.2%. Conclusions: LAAO is a safe and effective approach in CKD patients. Given the increased risk of bleeding and contraindications to oral anticoagulation, CKD patients might be good candidates for LAA occlusion.